Methionine synthase deficiency: Variable clinical presentation and benefit of early diagnosis and treatment. Issue 2 (21st October 2021) - Kripps, Kimberly A.; Sremba, Leighann; Larson, Austin A.; Van Hove, Johan L.K.; Nguyen, Hoanh; Wright, Erica L.; Mirsky, David M.; Watkins, David; Rosenblatt, David S.; Ketteridge, David; Berry, Susan A.; McCandless, Shawn E.; et al.
Abstract: Methionine synthase deficiency ( cblG complementation group) is a rare inborn error of metabolism affecting the homocysteine re‐methylation pathway. It leads to a biochemical phenotype of hyperhomocysteinemia and hypomethioninemia. The clinical presentation of cblG is variable, ranging from seizures, encephalopathy, macrocytic anemia, hypotonia, and feeding difficulties in the neonatal period to onset of psychiatric symptoms or acute neurologic changes in adolescence or adulthood. Given the variable and nonspecific symptoms seen in cblG, the diagnosis of affected patients is often delayed. Medical management of cblG includes the use of hydroxocobalamin, betaine, folinic acid, and in some cases methionine supplementation. Treatment has been shown to lead to improvement in the biochemical profile of affected patients, with lowering of total homocysteine levels and increasing methionine levels. However, the published literature contains differing conclusions on whether treatment is effective in changing the natural history of the disease. Herein, we present five patients with cblG who have shown substantial clinical benefit from treatment with objective improvement in their neurologic outcomes. We demonstrate more favorable outcomes in our patients who were treated early in life, especially those who were treated before neurologic symptoms manifested. Given improved outcomes from treatment of presymptomatic patients, cblG warrants inclusion in newborn screening.